Asthma and wheezing among Norwegian elite athletes - Nystad, W.; Harris, J.; Sundgot-Borgen, J. (Medicine & Science in Sports & Exercise, 2000)
Purpose: The objectives were to estimate the prevalence of self-reports of asthma and wheezing among Norwegian elite athletes compared with the general population and to estimate the associations between asthma and types of sports, exercise and team level. Methods: The study population included all Norwegian elite athletes on the national junior and senior teams in 1997 (N = 1620) and a random sample from the general population (N = 1680). The surveys included items for asthma, respiratory symptoms, the history of participation in sports, sports events, and exercise and team level. The associations between the exposure variables and the outcomes adjusting for potential confounding factors were estimated using logistic regression. Crude (c) and adjusted odds ratio (aOR) with 95% confidence interval (CI) are presented. Results: The prevalence of asthma was greater among athletes (10.0%) compared with that in the general population (6.9%) and remained so after controlling for confounders, aOR = 1.5 (95%CI 1.1-2.1). The risk of asthma was highest in sports requiring strength and endurance. This was the case for comparisons between athletes and the general population, aOR = 3.5 (1.6-7.6) for strength and aOR = 2.2 (1.4-3.5) for endurance sports. Comparisons within the sample of athletes using technical sports as the reference category revealed similar results, aOR = 3.0 (1.1-8.0) and aOR = 2.0 (1.0-4.3), respectively. Furthermore, asthma was more common among female than male athletes (aOR 1.7 (1.1-2.7)). Training more than 20 h·wk-1 was associated with asthma when compared with levels of training less than 10 h·wk-1 (aOR 1.9 (1.0-4.1)). Conclusion: These results indicate that asthma is more common among athletes compared with the general population. Asthma among athletes may define a subgroup of asthma cases for whom etiology is related to extensive exercise.